2006
DOI: 10.1029/2005jc003450
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of signals in basin‐scale ocean bottom pressure from a barotropic model

Abstract: [1] The exchange of atmospheric plus oceanic mass between ocean basins is investigated using a global barotropic ocean model. We find two particular cases of exchange between two basins. At periods of 4-6 days, the exchange is between the Atlantic and Pacific basins, and represents a known oscillation forced by atmospheric pressure. This mode represents a failure of the inverse-barometer relationship due to the large scale and high frequency of atmospheric forcing, and the presence of continents. Significant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 32 publications
3
37
0
1
Order By: Relevance
“…If this also occurs at our latitudes, any net northward transports associated with these barotropic pressure perturbations are likely to be smaller than the 12.5 Sv number estimated above when the eastern boundary is constant. Nevertheless, these perturbations still produce net meridional transports across latitudes, on synoptic atmospheric time scales associated with global oscillations of masses between ocean basins (Stepanov and Hughes 2006). Detection of these signals, and their spatial coherence over large distances, demonstrates that the instruments are producing good quality data and are capable of detecting propagating signals.…”
Section: April 2013 E L I P O T E T a Lmentioning
confidence: 99%
“…If this also occurs at our latitudes, any net northward transports associated with these barotropic pressure perturbations are likely to be smaller than the 12.5 Sv number estimated above when the eastern boundary is constant. Nevertheless, these perturbations still produce net meridional transports across latitudes, on synoptic atmospheric time scales associated with global oscillations of masses between ocean basins (Stepanov and Hughes 2006). Detection of these signals, and their spatial coherence over large distances, demonstrates that the instruments are producing good quality data and are capable of detecting propagating signals.…”
Section: April 2013 E L I P O T E T a Lmentioning
confidence: 99%
“…With simultaneous observations of OBP in different locations, the barotropic mass transport between the locations may be determined (Wearn and Baker 1980;Morison 1991). Ocean mass transport may be used to study overturning flow variations (Roussenov et al 2008), mass exchange between ocean basins (Hughes and Stepanov 2004;Stepanov and Hughes 2006;Chambers and Willis 2009), and freshwater changes in the ocean (Morison et al 2007(Morison et al , 2012. On a broader scale, changes in mass, and therefore changes in OBP, are directly related to water mass exchanges among the ocean, cryosphere, and hydrosphere (Wahr et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies based on models demonstrated there are large-scale redistributions of mass within the ocean at periods of a year or shorter [282,277,283], interannual variations were considered suspect due to potential drift in the models. Chambers and Willis [284], however, demonstrated large, coherent mass exchanges between the Indo-Atlantic and Pacific oceans, on time-scales longer than 1-year ( Figure 27).…”
Section: Grace and The Ocean: More Than Sea Level Risementioning
confidence: 99%